2020
DOI: 10.3390/ijms22010083
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokines Perturb Mouse and Human Pancreatic Islet Circadian Rhythmicity and Induce Uncoordinated β-Cell Clock Gene Expression via Nitric Oxide, Lysine Deacetylases, and Immunoproteasomal Activity

Abstract: Pancreatic β-cell-specific clock knockout mice develop β-cell oxidative-stress and failure, as well as glucose-intolerance. How inflammatory stress affects the cellular clock is under-investigated. Real-time recording of Per2:luciferase reporter activity in murine and human pancreatic islets demonstrated that the proinflammatory cytokine interleukin-1β (IL-1β) lengthened the circadian period. qPCR-profiling of core clock gene expression in insulin-producing cells suggested that the combination of the proinflam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 91 publications
3
25
0
Order By: Relevance
“…Consistent with recent observations [ 19 , 20 ], our data reveal an upregulation of REV-ERBα in β-cells exposed to diabetes-related conditions. REV-ERBα is a transcriptional repressor that has been shown to negatively regulate the expression of genes involved in many important cellular processes such as metabolism, inflammation, proliferation, and notably, plays an important role in the stabilization of the core circadian clock transcriptional-translational feedback look.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with recent observations [ 19 , 20 ], our data reveal an upregulation of REV-ERBα in β-cells exposed to diabetes-related conditions. REV-ERBα is a transcriptional repressor that has been shown to negatively regulate the expression of genes involved in many important cellular processes such as metabolism, inflammation, proliferation, and notably, plays an important role in the stabilization of the core circadian clock transcriptional-translational feedback look.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with its role as a transcriptional repressor, REV-ERBα was recently shown to negatively regulate autophagy flux through transcriptional repression of key genes involved in vesicle nucleation, autophagosomal formation, lysosomal function, and mitophagy [ 18 ]. Correspondingly, pharmacological activation of REV-ERBα has been reported to inhibit autophagy and induce apoptosis in cancer cells [ 17 ], impair insulin secretion, and promote cell apoptosis in β-cell lines [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperactive macrophages secrete less IL-1b than macrophages undergoing pyroptosis, which fits with our observation that IL-1b secretion upon stimulation with the MAC occurs to a lesser extent than in nigericin-stimulated cells. Importantly, low levels of IL-1b are able to activate downstream signaling pathways in target cells (41)(42)(43)(44)(45) suggesting that the levels of MAC-mediated inflammasome activation and IL-1b release seen in our experiments can be biologically important.…”
Section: Discussionmentioning
confidence: 73%
“…We and others [24, 25] have recently found that proinflammatory cytokines reconfigure the expression pattern of core-clock genes, while also changing rhythmic parameters in islets harboring a Period2 promotor-driven Luciferase ( Per2-Luc ). We found that the proinflammatory cytokines Interleukin-1β (IL-1β) and Interferon-γ (IFN-γ) increased period length in both human and murine reporter islets [24].…”
Section: Introductionmentioning
confidence: 99%